2014
DOI: 10.1038/srep05830
|View full text |Cite
|
Sign up to set email alerts
|

Social cycling and conditional responses in the Rock-Paper-Scissors game

Abstract: How humans make decisions in non-cooperative strategic interactions is a big question. For the fundamental Rock-Paper-Scissors (RPS) model game system, classic Nash equilibrium (NE) theory predicts that players randomize completely their action choices to avoid being exploited, while evolutionary game theory of bounded rationality in general predicts persistent cyclic motions, especially in finite populations. However as empirical studies have been relatively sparse, it is still a controversial issue as to whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
125
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(143 citation statements)
references
References 45 publications
(64 reference statements)
17
125
1
Order By: Relevance
“…Choice history biases are evident in a variety of situations even when they are maladaptive (5). A possibility is that subjects are applying strategies that lead to optimal decisions in their natural environment, but those same strategies become fallacies when faced with the artificial constrains of psychophysical experiments (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choice history biases are evident in a variety of situations even when they are maladaptive (5). A possibility is that subjects are applying strategies that lead to optimal decisions in their natural environment, but those same strategies become fallacies when faced with the artificial constrains of psychophysical experiments (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…We then selected the Λ value that produced the highest likelihood. The likelihood was computed as LH = ∏zðtÞ, [5] where t refers to trial number and zðtÞ corresponds to…”
Section: Methodsmentioning
confidence: 99%
“…Zhijian Wang observed that winning players stick to their one winning strategy while losing players changes strategies [21]. Psychology has conceptualize the "conditional response" [22] and game theory has the "Pavlov strategy" [23].…”
Section: Publications In Roshambomentioning
confidence: 99%
“…Here the decision making of each agent is dependent upon the outcome of the game at the previous step as it adopts the winners' choices based on local information. The higher probability for agents to keep the choices won in the last round can be considered as a conditional response behavior [32] in the multiagent interaction setting. If the winning-resource set is empty, agent i will randomly select one from the k available resources.…”
Section: Multiresource Mg-dynamics Modelmentioning
confidence: 99%